LAND REFORM-REFORM AGRARIA-REDISTRIBUSI LAHAN PERSPEKTIF PASAL 33 AYAT 3 UUD 1945 - Soeprijanto, Troeboes (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2023)
The earth, water, space, and natural wealth contained in it are bonus demogration given to all Indonesian people and nations, which is the grace and gift of God Almighty. Therefore, the State as an organization of power through the government apparatus which is mandated and mandated to regulate, organize, and manage the grace of God Almighty for the realization of the prosperity of all Indonesian people (article 2 paragraph 1 of Law 5 of 1960 according to the concept of social prosperity). To realize this social prosperity, of course, it must be accompanied by legal prosperity, so that an equitable policy on land rights will be created for all Indonesians. Through land reform with its agrarian reform and land redistribution at the same time with PRONA and PTSL, at least it provides a basic concept of direction with their respective specificities, which have been implemented can lead to the goals as in article 33 paragraph 3 of the 1945 Constitution. However, the concept of Land reform and the agrarian reform program and land redistribution through prona and PTSL have a correlation, where the correlation is not balanced. Supposedly, the correlation between these two things at least contributes to the increase in the level of prosperity for all Indonesians through the land sector(social prosperity). This research is literature research using a mixed method between qualitative and quantitative. The approach used is a civil law approach based on the 1945 Constitution. The result of this study is to restore specific programs such as Prona or PTSL so that they can be continued, which are aimed at other community groups that have a wider scope of social strata as an equal distribution of legal justice in the Indonesian state.